Perancangan Aplikasi Game Warung Sate Lilit Bali Berbasis Android Sebagai Media Pembelajaran Pengenalan Sate Lilit Secara Sederhana - I Made Ageng Suyasa; Putu Wira Buana; I Ketut Adi Purnawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Udayana, 2017)
The typical food of an area is one of the cultural heritage of regions that should be preserved and maintained so the extinction never crushed by the time. Sate lilit is one of the typical foods in Bali. Sate lilit is processed by meats that are chopped and blended using a wide range of the balinese wrapped around or taped in a stalk of bamboo and then baked in hot coals. Warung Sate lilit game are aiming to introduce the general public and younger generation in particular how to make sate in a simple one turn, as well as aimed at the medium of learning are expected to support the preservation of sate lilit of Bali. Warung Sate Lilit Bali game is expected to increase the interest of the younger generation about satay lilit as the typical food of Bali. Warung Sate Lilit Bali game be played by the drag and drop method, so the user simply choose the materials provided by, then comes the bar to determine the dose of materials that are required to fulfill orders from buyers. Warung Sate Lilit Bali game are provide learning via the information contained on the menu ingredient which has been available and also get learning to play, because at the time to drag and drop the materials, the players knowing what course the necessary materials for making the sate lilit turn a simple.